Adenoma detection by Endocuff-assisted versus standard colonoscopy in routine practice: a cluster-randomised crossover trial. Issue 12 (24th March 2020) - Karsenti, David; Tharsis, Gaelle; Perrot, Bastien; Cattan, Philippe; Tordjman, Gilles; Venezia, Franck; Zrihen, Elie; Gillot, Dominique; Gillet, Agnes; Hagege, Charles; Samama, Joelle; Etienney, Isabelle; et al.
Abstract : Objective: Endocuff Vision (ECV) is the second generation of a device designed to improve polyp detection. The aim of this study was to evaluate its impact on adenoma detection rate (ADR) in routine colonoscopy. Design: This cluster-randomised crossover trial compared Endocuff-assisted (ECV+) with standard (ECV-) colonoscopy. Two teams of 11 endoscopists each with prior ECV experience, balanced in terms of basal ADR, gender and case volume were compared. In randomised fashion, the teams started with ECV+ or ECV- and switched group after inclusion of half of the cases. The main outcome criterion was ADR difference between ECV+ and ECV-. Subgroup analysis was done for physicians with low and high ADR (< or ≥ 25%). Results: During two periods of 20 and 21 weeks, respectively, the 22 endoscopists included 2058 patients (1032 ECV- vs 1026 ECV+, both groups being comparable). Overall ADR for both groups taken together was higher with ECV (39.2%) than without (29.4%; p<0.001) irrespective of the sequence of use (ECV+ or ECV- first), but mostly in adenomas <1 cm. In the physician subgroup analysis, only high detectors showed a significant ADR increase (from 31% to 41%, p<0.001), while the increase in the low detectors was not significant (from 24% to 30%, p=0.11). ECV had a positive impact in all colonic locations, except for the rectum. No ECV- related complication was reported. Conclusion: We observed a significant ADR difference of approximately 10% by the use of ECV. By subgroup analysis, this increase was significant only in physicians classified as high detectors. Trial registration number: ClinicalTrials.gov (NCT03344055 ).